Algeria Economic Monitor, Fall 2020 : Navigating the COVID-19 Pandemic, Engaging Structural Reforms - World Bank Group (World Bank, Washington, DC, 2021)
This report presents an overview of Algeria’s recent macroeconomic developments and of its short-term economic outlook. The report is divided into two chapters. Chapter one presents the country’s macroeconomic developments in 2019, which establishes the context for the unprecedented developments of 2020 related to the Coronavirus 2019 (COVID-19) pandemic. Chapter two details the impact of the COVID-19 pandemic and concurrent crash in oil prices on various dimensions of Algeria’s economic fabric. Finally, the conclusion presents the short-term outlook for the Algerian economy.